Autocorrelation R2 on Mars. Issue 17 (12th September 2022) - Deng, Sizhuang; Levander, Alan
Abstract: A purpose of the Interior Exploration Using Seismic Investigations, Geodesy and Heat Transport (InSight) mission is to reveal the Martian interior structure with seismic data. In this work, ambient noise autocorrelation of the continuously recorded vertical‐component seismic signals has extracted the Rayleigh waves that propagate around Mars for one cycle, R2 . The Mars orbiting surface waves are observed at a lag time of ∼6, 000 s in the stacked autocorrelation series filtered between 0.005 and 0.01 Hz. Synthetic seismograms from a set of radially concentric velocity models were computed to find the best‐fitting one as the starting model for a Monte Carlo inversion. The starting model was randomly perturbed iteratively to increase the correlation coefficients and reduce the absolute time shifts between the synthetic and observed R2 . An S‐wave low‐velocity layer in the inverted velocity model extends to ∼400 km depth, consistent with Marsquake observations, geophysical inversion, and high‐pressure experiments. Plain Language Summary: The subsurface structures of Earth are imaged by the detailed analysis of seismic data recorded by thousands of stations deployed on the Earth's surface. The Interior Exploration Using Seismic Investigations, Geodesy and Heat Transport (InSight) mission landed a seismograph on Mars, which was deployed at the end of 2018 to investigate the planet's interior structure and dynamic evolution. In this study, we preprocessed the continuous vertical‐component seismic data, and by autocorrelation retrieved a Rayleigh wave, one class of seismic surface wave, that orbits Mars. Rayleigh wave group velocities between 115 and 200 s period were measured from the observed Mars orbiting Rayleigh waves. Synthetic seismograms were calculated using current estimates of the velocity structure of Mars for comparisons to the observation. The spherically symmetric model was updated with a Monte Carlo algorithm, an inversion method that randomly perturbs the velocity model and determines the model that best matches the Mars orbiting surface waves through trial and error. An S‐wave low‐velocity zone is observed to the depth of ∼400 km beneath the Martian surface, consistent with other InSight seismic observations and velocity models measured from geophysical modeling and high‐pressure laboratory experiments. Key Points: The R2 surface waves on Mars are recovered by low‐frequency ambient noise autocorrelation of Interior Exploration Using Seismic Investigations, Geodesy and Heat Transport (InSight) seismic data An updated upper mantle velocity model is developed using a Monte Carlo method to fit the observed R2 surface waves on Mars The S‐wave low velocity zone extends to ∼400 km depth, consistent with the results from previous studies